Sustainable preservation : greening existing buildings - Carroon, Jean.; Moe, Richard (Hoboken, New Jersey : John Wiley & Son, Inc., 2010)
Sustainable Preservation takes a nuanced look at the hundreds of choices that adaptive reuse requires architects to make$1 (Bfrom ingenious ways to redeploy existing structural elements to time-honored techniques for natural ventilation to creation of wetlands that restore a site's natural biological functions. In addition, Sustainable Preservation presents 50 case studies of projects$1 (Bschools, houses, offices, stores, museums, and government buildings$1 (Bthat set new standards for holistic approaches to adaptive reuse and sustainability. The author covers design issues, from building location to lighting systems, renewable power options, storm water handling, and building envelope protection and integrity. The book also reviews operational issues, including materials choices for low lifetime maintenance, green housekeeping, and indoor air quality.s
1. Buildings and Environmental Stewardship - Understanding the Issues -- 2. Buildings and Sustainable Development - Understanding the Goals -- 3. Tools, Guidelines, and Process - Balancing the Goals -- 4. Water and Site -- 5. Energy - Not Only Issue But -- 6. Indoor Health - Light, Air and Health -- 7. Materials and Resources - Reduce, Repair, Reuse, Recycle -- 8. Best Practices - Operations, Maintenance, and Change -- 9. Houses -- 10. The Recent Past.
Includes bibliographical references and index.
Keywords: SUSTAINABLE ARCHITECTURE -- UNITED STATES -- CASE STUDIES